Gambaran Dermatoglifi Tangan Pasien Skizofrenia di Rumah Sakit Jiwa Sambang Lihum Martapura Kalimantan Selatan - Panghiyangani, Roselina; Husein, Achyar Nawi; Nazar, Hasrul (Jurnal Kedokteran Indonesia, 2009)
Background: Hand dermatogliphic is a pattern of skin ridges in hand radius and palm. Skizophrenia is apsychosis with disturbance in personality, distorted thought, and perception disturbance. However,cognitive and intellectual capacity are usually not disturbed. This study aimed to describe handdermatogliphic profile of skizophrenic patients and compare it with non-skizofrenia persons.Methods: An analytic study was conducted at Sambang Lihum Mental Hospital Martapura, SouthKalimantan. 32 skizophrenic patients were taken as study subjects, and 32 persons without skizophreniaas control. The data was analyed using chi square test for finger ridge pattern and independent t testfor total finger ridge count and fluctuating asymmetry.Results: There was statistically significant difference in finger ridge pattern (p<0.05) . There was nostatistically significant difference in total fingger ridge count (p>0.05) and in fluctuating asymmetry(p>0.05).Conclusion: There is statistically significant difference in finger ridge pattern between skizophrenicpatients and non-skizophrenic persons.Keywords: skizofrenia, finger ridge pattern, total finger ridge count, fluctuating asymmetry